ADAT PERNIKAHAN RASAN TUHA DI DESA SUKA NEGERI KECAMATAN SEMENDAWAI BARAT KABUPATEN OGAN KOMERING ULU TIMUR TAHUN 1995-2015 - Saigantha, Akbar Iwayan; Sair, Alian; Syarifuddin, Syarifuddin (Journal of Indonesian History, 2019)
The title of this study was "The Traditional Marriage of Rasan Tuha in Suka Negeri Village, West Semendawai District, Regency of East Ogan Komering Ulu in 1995-2015 (The contribution of Class X Indonesian History Teaching Material in Senior High School 14 Palembang)". The purpose of this study was to reveal and explain the process of the implementation of Rasan Tuha wedding ceremonies in Suka Negeri village in 1995-2015, how the changes took place in the community and the factors that caused the changes happened in the community of Rasan Tuha wedding ceremonies. While the technique or method used for this study was a historical research method, that was the process of collecting data through literature study and in-depth interviews with some of the oldest indigenous people and communities. While the approach used was the anthropological approach and the sociological approach. Based on the results of data collection in the field, there have been changes in the procession of Rasan Tuha's wedding traditional ceremony in Suka Negeri village. The changes of some forms was happened in the procession of betunggu, pengatu, nyawak, bhumiah / ningkuk, ngarogoh turun sosat, mumpung, mungian nyumbah, butimbang, takad-takatan, tabur beras kunyit, and ngunut. The cause of the changes of traditional wedding ceremony of Rasan Tuha in Suka Negeri village was a change in mindset, population mobility, technological progress and economic factors. Keywords: The Changes of traditional ceremonies, Rasan Tuha wedding